Electrochemical Performance Studies of MnO2 Nanoflowers Recovered from Spent Battery - Ali, Gomaa A. M.; Ling, Tanling; Rajan, Jose; M. M., Yusoff; K. F., Chong (Elsevier, 2014)
The electrochemical performance of MnO2 nanoflowers recovered from spent household zinc–carbon battery is studied by cyclic voltammetry, galvanostatic charge/discharge cycling and electrochemical impedance spectroscopy. MnO2 nanoflowers are recovered from spent zinc–carbon battery by combination of solution leaching and electrowinning techniques. In an effort to utilize recovered MnO2 nanoflowers as energy storage supercapacitor, it is crucial to understand their structure and electrochemical performance. X-ray diffraction analysis confirms the recovery of MnO2 in birnessite phase, while electron microscopy analysis shows the MnO2 is recovered as 3D nanostructure with nanoflower morphology. The recovered MnO2 nanoflowers exhibit high specific capacitance (294 F g−1 at 10 mV s−1; 208.5 F g−1 at 0.1 A g−1) in 1 M Na2SO4 electrolyte, with stable electrochemical cycling. Electrochemical data analysis reveal the great potential of MnO2 nanoflowers recovered from spent zinc–carbon battery in the development of high performance energy storage supercapacitor system.